An upper bound of the number of tests in pooling designs for the error-tolerant complex model - Chen, Hong-Bin; Fu, Hung-Lin; Hwang, Frank K. (My University, 2008)
Recently pooling designs have been used in screening experiments in molecular biology. In some applications, the property to be screened is defined on subsets of items, instead of on individual items. Such a model is usually referred to as the complex model. In this paper we give an upper bound of the number of tests required in a pooling design for the complex model (with given design parameters) where experimental errors are allowed.
Keywords: Pooling designs; Nonadaptive algorithms; Disjunct matrices